False-positive test results for syphilis in relatives of a patient with systemic lupus erythematosus. Issue 4 (August 1979) - Jessop, S; Botha, P
Abstract : In a family of nine members, two had systemic lupus erythematosus and seven positive serological test results for syphilis. None of the affected subjects had a history or physical signs of syphilis, but two had positive results to the Treponema pallidum immobilisation test. The explanation for these findings is not known, but possibily they were all false-positive reactions.